2023
DOI: 10.1038/s41598-023-32356-3
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal risk associated with finasteride versus dutasteride among men treated for benign prostatic hyperplasia: nationwide cohort study

Abstract: Finasteride, a 5α-reductase inhibitor used in benign prostatic hyperplasia and androgenetic alopecia, has been associated with an increased suicidal risk, whereas it is unclear whether such risk is similar to that for another 5α-reductase inhibitor, dutasteride. We aimed to assess the risk of suicidal behaviours with finasteride relative to dutasteride. A nationwide cohort study was conducted using the French National Health Data System (SNDS). Men aged 50 years or older initiating finasteride 5 mg or dutaster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Alarmingly, former finasteride users had a marked increase in suicidal thoughts (44%) compared to nonusers (3%), 54 which may be particularly relevant for a subset of patients with a history of mood disorders. 57 Fewer studies have explored the relationship between anxiety and finasteride usage, but self-reports indicate a comparable number of patients experiencing anxiety (73%) as depression (74%). 58 Preclinical studies have demonstrated that treating rodents with finasteride increases depressive and anxiety phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Alarmingly, former finasteride users had a marked increase in suicidal thoughts (44%) compared to nonusers (3%), 54 which may be particularly relevant for a subset of patients with a history of mood disorders. 57 Fewer studies have explored the relationship between anxiety and finasteride usage, but self-reports indicate a comparable number of patients experiencing anxiety (73%) as depression (74%). 58 Preclinical studies have demonstrated that treating rodents with finasteride increases depressive and anxiety phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated an association between finasteride use and the incidence of depression (Altomare & Capella, 2002;Irwig, 2012;Rahimi-Ardabili, Pourandarjani, Habibollahi, & Mualeki, 2006;Welk et al, 2017) (for review see (Hirshburg et al, 2016)). Alarmingly, former finasteride users had a marked increase in suicidal thoughts (44%) compared to non-users (3%) (Irwig, 2012) which may be particularly relevant for a subset of patients with a history of mood disorders (Laanani, Weill, Jollant, Zureik, & Dray-Spira, 2023). Fewer studies have explored the relationship between anxiety and finasteride usage but self-reports indicate a comparable number of patients experiencing anxiety (73%) as depression (74%) (Walf, Kaurejo, & Frye, 2018).…”
Section: Endogenous Neurosteroids and Affective Tonementioning
confidence: 99%